1990
DOI: 10.1093/oxfordjournals.bmb.a072388
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and treatment of obstructive airways disease in the elderly

Abstract: Airways obstruction is a common problem in the elderly and may be overlooked because of the high prevalence of other disorders such as cardiac failure that have similar presentations. Identification of airways obstruction and assessment of responsiveness to treatment would be improved if simple tests of pulmonary function were performed on a routine basis in elderly patients complaining of respiratory symptoms. In the treatment of airways obstruction, particular attention needs to be paid to the patients' inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a longitudinal survey study of respiratory disease, Burrows et al (8) showed that among asthmatic patients newly diagnosed over the age of 60, two-thirds had respiratory symptoms, and one-third had obstructive defects in lung function for a mean period of 8.5 years prior to the diagnosis. The reasons for this delay in diagnosis are unexplained but several factors may contribute including changes in perception of disease with increasing age (9). Elderly asthmatics are also prone to more frequent and longer hospital stays (10), and it is thought that they have a greater risk of asthma death (11,12).…”
Section: Diagnosis Of Asthmamentioning
confidence: 99%
“…In a longitudinal survey study of respiratory disease, Burrows et al (8) showed that among asthmatic patients newly diagnosed over the age of 60, two-thirds had respiratory symptoms, and one-third had obstructive defects in lung function for a mean period of 8.5 years prior to the diagnosis. The reasons for this delay in diagnosis are unexplained but several factors may contribute including changes in perception of disease with increasing age (9). Elderly asthmatics are also prone to more frequent and longer hospital stays (10), and it is thought that they have a greater risk of asthma death (11,12).…”
Section: Diagnosis Of Asthmamentioning
confidence: 99%
“…Because of the dif ficulty in precisely defining asthma, true inci dence and prevalence are unknown, but an approximate prevalence of 20% in elderly people has been reported [11], However, Banerjee et al [2] have reported an incidence of asthma of over 40% in an elderly population (age, range 55-91 years) attending day hospi tal or living in welfare homes. These authors recorded FEVi, FVC, and peak expiratory flow rate (PEFR) before and 5 min after inha lation of 200 pg salbutamol.…”
Section: Asthm a In The Elderlymentioning
confidence: 99%